Manipulation of Phytohormone Pathways by Effectors of Filamentous Plant Pathogens - Han, Xiaowei; Kahmann, Regine (Frontiers in Plant Science, 2019)
Phytohormones regulate a large variety of physiological processes in plants. In addition, salicylic acid (SA), jasmonic acid (JA) and ethylene (ET) are responsible for primary defense responses against abiotic and biotic stresses while plant growth regulators, such as auxins, brassinosteroids (BRs), cytokinins (CKs), abscisic acid (ABA) and gibberellins (GAs), also contribute to plant immunity. To successfully colonize plants, filamentous pathogens like fungi and oomycetes have evolved diverse strategies to interfere with phytohormone pathways with the help of secreted effectors. These include proteins, toxins, polysaccharides as well as phytohormones or phytohormone mimics. Such pathogen effectors manipulate phytohormone pathways by directly altering hormone levels, by interfering with phytohormone biosynthesis or by altering or blocking important components of phytohormone signaling pathways. In this review we outline the various strategies used by filamentous phytopathogens to manipulate phytohormone pathways to cause disease.